2010
DOI: 10.1158/1055-9965.epi-09-0381
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Sex Steroid Hormones in Nipple Aspirate Fluid during the Menstrual Cycle and after Menopause in Relation to Serum Concentrations

Abstract: Previous studies have shown that progesterone concentrations in serum and nipple aspirate fluid (NAF) are significantly correlated in premenopausal women, but estradiol concentrations are not. We therefore sought to ascertain the patterns of both steroids in NAF throughout the menstrual cycle and in postmenopausal women. Simultaneous samples of blood and NAF were obtained from 40 premenopausal and 16 postmenopausal women. Premenopausal samples were backdated from the following menstrual period. Steroids were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 18 publications
(22 reference statements)
5
19
0
Order By: Relevance
“…We found a correlation of 0.29 with NAF [7]; Maskarinec et al [18] found r = 0.37. In addition to the obvious fluctuations of serum estradiol, we found that NAF estradiol had a pattern during the menstrual cycle that was different from that in serum [12].…”
Section: Associations Of Naf Dlf and Rfna Concentrations Of Estradimentioning
confidence: 65%
See 2 more Smart Citations
“…We found a correlation of 0.29 with NAF [7]; Maskarinec et al [18] found r = 0.37. In addition to the obvious fluctuations of serum estradiol, we found that NAF estradiol had a pattern during the menstrual cycle that was different from that in serum [12].…”
Section: Associations Of Naf Dlf and Rfna Concentrations Of Estradimentioning
confidence: 65%
“…The lipid residue from the NAF and DLF samples was extracted into ethyl acetate-hexane (3:2). The estrogens were either separated by the alkaline partition method [9] or by HPLC [12]. In the solvent partition method estradiol is extracted from the NAF or concentrated DLF samples into ethyl acetate-hexane (3:2) and, after evaporation of the solvent, the residue is partitioned between 0.4 N aq.…”
Section: Analysis Of Naf and Dlf For Estrogensmentioning
confidence: 99%
See 1 more Smart Citation
“…When results in the present study are compared with our previous publications, it is true that estradiol concentrations in NAF have been consistently, but not significantly, lower in postmenopausal women than in premenopausal women. The number of postmenopausal subjects in our 2010 and 2004 publications was 18 in each (1,2). The higher postmenopausal NAF estradiol concentrations in the present study (3), although unexpected, can be attributed to chance when the sample size is small, as it was here, with 8 NAF-yielding postmenopausal subjects in the soy group.…”
supporting
confidence: 43%
“…Demographic information of subjects used for analysis from both studies was summarized in Table 1. The true menopausal status (TMS) was determined using last menstrual period (LMP) date, plasma estradiol (E2), progesterone (P4), and follicle-stimulating hormone (FSH) concentrations, measured by radioimmunoassay, and enzyme immunoassay as described previously [7]. Hormonal criteria for TMS classification were FSH [ 30 mIU/ ml, and E2 \ 30 pg/ml, P4 \ 3 ng/ml.…”
Section: Subjectsmentioning
confidence: 99%